The Geographic Analysis of Poverty Indicators in Kirkuk Governorate for the Year 2021 - Hamad, Sameen Jihad; Hassan, Tofan Sattam (Journal of Tikrit University for Humanities, 2024)
The Human Poverty Index (HPI) is an indicator of the poverty of a society, which was developed by the United Nations to complement the Human Development Index (HDI) and was announced for the first time as part of the Human Deprivation Report in 1997, which better explains the extent of deprivation in deprived countries compared with the human development index. The poverty line measure has been developed and approved, which is one of the most important methods for measuring the poverty index, through which the numbers of poor people were determined, as it is the dividing line that distinguishes between the poor class and others. This line was determined by the Central Bureau of Statistics for the year 2020, and the cost of this line was estimated at approximately (150). One thousand Iraqi dinars per month per person. Based on this line, the number of poor people and poverty levels were determined, as poverty is nothing but the result of an economic problem that affects most societies without discrimination, which is unemployment, as the unemployment problem is considered one of the most serious facing underdeveloped countries currently. The seriousness of the problem is highlighted by the increasing number of unemployed people, which leads to the waste of the human labor component, resulting in negative economic, social and political effects.